The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1103/physrevlett.41.1328
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Propagation of an Intense Rotating Proton Beam

Abstract: The theoretically favorable plasma-confinement properties of field-reversed magnetic field configurations have led to many reactor proposals. 1 " 5 Such configurations have been experimentally realized (i) by the injection of relativistic electron beams 6 to form a reversed-field electron ring, 7 (ii) by plasma currents induced by relativistic-electron-beam injection, 8 and (ill) by reversed-field 0 pinches. 9 However, synchrotron-radiation energy losses make a relativistic electron ring unsuitable for a fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1981
1981
1984
1984

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
(3 reference statements)
0
12
0
Order By: Relevance
“…A schematic of the system which approximates closely the experimental arrangement of Dreike et al [22][23][24] is shown in Fig. 2.2.…”
Section: Numerical Simulations Of Injection and Trapping Of Ion Ringsmentioning
confidence: 84%
See 2 more Smart Citations
“…A schematic of the system which approximates closely the experimental arrangement of Dreike et al [22][23][24] is shown in Fig. 2.2.…”
Section: Numerical Simulations Of Injection and Trapping Of Ion Ringsmentioning
confidence: 84%
“…Thus, it is important to minimize the axial thermal spread. For injection through a magnetic cusp, this can be achieved by arranging the ion emitting surface to coincide with a flux surface (Dreike et al [22][23][24]). Humphries [79a] has summarized some of the problems associated with the formation of proton rings.…”
Section: Fig23 Transmission Coefficient T As a Function Of (A) Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermofax paper witness targets show its mean radius is 10 cm and its thickness is 6 cm. When the beam is injected into vacuum (< 10" 3 Torr), it is radially and axially dispersed on a \ m distance scale, despite the presence of surface flashover electron sources in the cusp region, as previously used, 4 indicating inadequate space-charge neutralization in the cusp.…”
mentioning
confidence: 89%
“…The proton source is an annular magnetically insulated diode, similar to one described previously. 4 Pulsed coils within the anode of the diode provide both closed magnetic-flux surfaces around the anode which insulate against electron flow and a cusplike transition to the solenoidal field, as shown in Fig. 1(b).…”
mentioning
confidence: 99%